Economic Analysis of a Pediatric Ventilator-Associated Pneumonia Prevention Initiative in Nicaragua - Edward I. Broughton; Sergio R. López; María Nela Aguilar; María Mercedes Somarriba; Magaly Pérez; Nieves Sánchez (International Journal of Pediatrics)
We performed an economic analysis of an intervention to decrease ventilator-associated pneumonia (VAP) prevalence in pediatric intensive care units (PICUs) at two Nicaraguan hospitals to determine the cost of the intervention and how effective it needs to be in order to be cost-neutral. A matched cohort study determined differences in costs and outcomes among ventilated patients. VAP cases were matched by sex and age for children older than 28 days and by weight for infants under 28 days old to controls without VAP. Intervention costs were determined from accounting and PICU staff records. The intervention cost was approximately $7,000 for one year. If VAP prevalence decreased by 0.5%, hospitals would save $7,000 and the strategy would be cost-neutral. The finding that the intervention required only modest effectiveness to be cost-neutral and has potential to generate substantial cost savings argues for implementation of VAP prevention strategies in low-income countries like Nicaragua on a broader scale.